Pelapisan Hidroksiapatit Pada Stainless Steel 316L Menggunakan Metode DIP Coating Dengan Variasi Rasio Binder Pati Sagu Dan Waktu Pengadukan - Hidayah, Putri Husni; Fadli, Ahmad; Amri, Amun (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Utilization of stainless steel 316L as bone implant could be done by coating hydroxyapatite on itâ€™s surface, to obtain a material with good biocompatibility and mechanical strength. The purpose of this research is to coating hydroxyapatite on stainless steel 316L using starch asbinder and understand the influence of binder ratio and stirring time on characters of coating hydroxyapatite deposited by dip coating method. Stainless steel was cut into size 2Ã—3cm2 and sterilized with acetone. The substrat then dipped into solution which consist of 10 gram hydroxyapatite, 20 gram aquadest and starch 1; 1,25 and 1,5 gram. The substrat wasdried at 110oC for 30 minutes and then sintered at 800oC for 1 hour. The result of SEM analysis showed that at 16 and 20 hour stirring time the coating thickness increased from 35Î¼m to 77 Î¼m. At 24 hour stirring time the obtained thickness was decrease to 60 Î¼m. The coating thickness decreased with binder ratio, at binder ratio addition the thickness obtainedwas 60 Î¼m, 58 Î¼m and 35 Î¼m, respectively. The shear strength was increase with binder ratio. While increasing stirring time decreased the shear strength. The highest shear strength obtained is 3,07 MPa. The layer that deposited on the substrat is contain 99,4% hydroxyapatite based on XRD analysis result.Keywords : Binder, Dip Coating, Hydroxyapatite, Stainless Steel.